Chronic kidney disease - The relevant information for an occupational physician - Marcin Renke; Jacek Parszuto; Marcin Rybacki; Wojciech Wołyniec; Przemysław Rutkowski; Bolesław Rutkowski; Jolanta Walusiak-Skorupa; Alicja Dębska-Ślizień (Nofer Institute of Occupational Medicine, 2018)
For a number of years chronic kidney disease (CKD) has been listed in the group of lifestyle diseases, such as obesity, diabetes, cardiovascular disease and hypertension. It is estimated that in Poland more than 4 million people may suffer from various stages of CKD. Chronic kidney disease may also be a consequence of all the other civilization diseases. At the same time it is worth noting that nephrological problems are increasingly being taken into account in modern medical certification. The aim of this work is, among other things, to improve safe access to the labor for patients with kidney diseases. In the legislation existing in our country since 2014 it is stated that chronic renal failure is a potential health contraindication to driving. Also in the annex to the Regulation of the Minister of Health dated 9 December 2015 on health conditions required for seafarers to work on a seagoing ship, it is said that ICD-10 codes (International Classification of Diseases) corresponding to acute and chronic renal failure (N17-N19) should be taken into account when qualifying employees to work at sea. Med Pr 2018;69(1):67-75